2005
DOI: 10.1037/0021-9010.90.5.857
|View full text |Cite
|
Sign up to set email alerts
|

After-Event Reviews: Drawing Lessons From Successful and Failed Experience.

Abstract: The claim that appropriate after-event review might decrease the relative advantage of drawing lessons from failures over drawing lessons from successes was examined in a quasi-field experiment. The results show that performance of soldiers doing successive navigation exercises improved significantly when they were debriefed on their failures and successes after each training day, compared with others who reviewed their failed events only. The findings also show that, before the manipulation, in both groups, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
285
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(294 citation statements)
references
References 73 publications
6
285
0
3
Order By: Relevance
“…A laboratory study on how to enhance individuals' ability to draw lessons from previous experiences found that after-event reviews of both successful and failed events had a positive impact on individual learning (Ellis and Davidi, 2005). The after-event reviews followed a similar but more extensive process than that of error management training because it also included successful events.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…A laboratory study on how to enhance individuals' ability to draw lessons from previous experiences found that after-event reviews of both successful and failed events had a positive impact on individual learning (Ellis and Davidi, 2005). The after-event reviews followed a similar but more extensive process than that of error management training because it also included successful events.…”
Section: )mentioning
confidence: 99%
“…Because of failure's significance, the research on the topic spans many fields such as psychology (cf. Ellis & Davidi, 2005;Hofmann & Mark, 2006), organizational studies (cf. Reason, 1997;Zhao & Olivera, 2006), strategic management (cf.…”
Section: Sometimes We May Learn More From a Man's Errors Than From Hmentioning
confidence: 99%
“…Errors have the potential to challenge individual mental models and thus provide starting points for modification of these models (Ellis and Davidi 2005;Frese and Zapf 1994;Kolodner 1983;Schank 1999). Such processes of modification can happen in different modes, e.g.…”
Section: Learning From Errorsmentioning
confidence: 99%
“…Given the prevalence of optimism among entrepreneurs (Puri & Robinson, 2006), success is more likely to be anticipated, whereas failures are more likely to be unanticipated. Ellis and Davidi (2005) find that people have more complex mental plans to explain failure, with longer causal paths and explanations, compared to how they reason about successes. Gino and Pisano (2011) point out that one of the difficulties of learning from success is exactly this so-called "failure-to-ask-why" syndrome, following the experiences of success.…”
Section: Literature Reviewmentioning
confidence: 89%
“…At the same time, Ellis and Davidi (2005) show that while failures catalyze epistemic processes such as hypothesis generation and information acquisition, successes tend to limit such processes. Based on a conducted experiment, the authors found that people tend to focus more on finding the reasons for failure than for successes.…”
Section: Literature Reviewmentioning
confidence: 99%